1993
DOI: 10.1021/bc00024a021
|View full text |Cite
|
Sign up to set email alerts
|

Biotinylated isocoumarins, new inhibitors and reagents for detection, localization, and isolation of serine proteases

Abstract: Eight new biotinylated, mechanism-based isocoumarin serine protease inhibitors have been designed and synthesized to detect, localize, and isolate serine proteases. Isocoumarins that contain a 4-chloro group, a biotinylated substituent at the 7-position, and different 3-alkoxy groups are inhibitors of various serine proteases including human leukocyte elastase (HLE), porcine pancreatic elastase (PPE), trypsin, human recombinant granzyme A, chymotrypsin, and cathepsin G. Insertion of spacers between the isocoum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 19 publications
0
49
0
2
Order By: Relevance
“…In addition, the specific activities of the purified enzyme and the recombinant CatA towards GS-7340 were virtually identical (35 nmol ⅐ min ÏȘ1 ⅐ g). DFP and 3,4-DCI are effective inhibitors of serine hydrolases, including CatA (6,11,17,22,26,32). Purified prodrug hydrolase and the recombinant CatA were both inhibited by 3,4-DCI and DFP with IC 50 s of Ïł0.5 M and 5 to 10 M, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the specific activities of the purified enzyme and the recombinant CatA towards GS-7340 were virtually identical (35 nmol ⅐ min ÏȘ1 ⅐ g). DFP and 3,4-DCI are effective inhibitors of serine hydrolases, including CatA (6,11,17,22,26,32). Purified prodrug hydrolase and the recombinant CatA were both inhibited by 3,4-DCI and DFP with IC 50 s of Ïł0.5 M and 5 to 10 M, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…However, this inhibitor displayed remarkable specificity for NTE in these experiments and thus appeared too selective to be useful as a general probe for serine hydrolases. Powers and colleagues had generated isocoumarin inhibitors coupled to biotin as serine hydrolase inhibitors (19,20). Although these isocoumarins reacted with a greater range of serine hydrolases than the aforementioned saligenin phosphoramidate, the requirement that these compounds alkylate a second functional group in the enzyme active site to achieve stable irreversible inhibition suggested that a significant number of serine hydrolases might show poor sensitivity to such reagents.…”
Section: Resultsmentioning
confidence: 99%
“…a-Aminoalkyl diphenyl phosphonate esters have been shown to be superb inactivators of serine proteases with no activity against cysteine proteases, are nontoxic in vivo, and are stable under physiological conditions [1,2]. Biotinylated aminoacyl chloromethanes and isocoumarins have found use as active-site-directed affinity labels for the disclosure of serine proteases from a variety of biological milieu and using techniques ranging from SDS-PAGE and Western blotting to immunocytochemistry and affinity purification [3][4][5][6]. We have previously reported on the synthesis of N-protected diphenyl phosphonate analogues of ornithine and lysine [7] and in this paper we detail the synthesis of the biotinylated analogues and report on their kinetic characterization and utilization for the detection of trypsin-like serine proteases using SDS-PAGE and Western blotting.…”
mentioning
confidence: 99%